Teenager’s Attitude Towards the Representatives of Opposite Sex within the Context of Their Own Spiritual Growth - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2006)
Gender differences can be essential (inborn) and randomly developed, the latter being preconditioned by ethnic, economic, social, political, religious, and geographical factors, and those differences help to establish inequality between the two sexes. With the democratic processes embracing more areas of human activity, issues of gender bias and discrimination appear among the topical ones; also, those issues come into focus of anthropological, physiological, psychological, and political research. In those studies, alongside the patterning of the randomly developed gender differences, there are noticeable attempts to oversimplify the treatment of the essential characteristics of the two sexes that make human existence essentially meaningful. The actual state of teenagers’ spiritual growth did not essentially have an effect on the teenagers’ attitudes towards the opposite sex as those attitudes in the first place depend on the teenagers’ attitudes towards the highest spiritual values. At the same time, the possible problems that can already be outlined are too complex for the pedagogues alone to solve them as the scope of the problems may shuffle the existential foundations of human being.